In-Depth Energy Analysis and Consumption Prediction of India (International Journal of Innovative Research in Computer Science & Technology, 2022)
Today's world requires extremely efficient  energy consumption. Demand is rising as a result of the  industrial sector's quick advancements, making energy  efficiency initiatives essential to reducing energy waste  and satisfying demand. According to the study of  numerous scenarios utilized by policy makers, at least a  50% reduction in industrial energy use is required for the  world temperature to rise by less than 2°C by the end of  this century. It is crucial that, we include a trustworthy  forecasting tool that can be used to estimate the energy  consumption based on numerous anticipated elements to remain on track with these scenarios and to meet the  desired objectives. Energy is recognized as a crucial  component for every country's economic development.  Energy is one of the main forces behind economic progress  in India, a growing nation. According to the review,  socioeconomic factors like GNP, energy prices, and  population are all related to energy usage. The impact of  socioeconomic factors on energy consumption is examined  in this article using econometric models. The R2, SE, test  is used to discover the best fit and to identify the important  factors affecting energy consumption. It has been shown  that demand for coal is influenced by population and coal  price, but demand for oil is influenced by GNP per capita.  The GNP and power price both affect how much electricity  is demanded. The projected demand for electricity, coal,  oil, and natural gas in India from 2030 to 2031 results in a  total energy need of 22.944 1015 kJ.
Keywords: Energy Consumption; India; Prediction; Renewable; Machine Learning